Analysis of clinical-instrumental correlations in patients with lumbar spinal stenosis - Fedotova, Inga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The purpose of the present work was to examine clinical-instrumental correlations in 317 patients suffering from lumbar spinal stenosis with/without neurological deficit. Clinical, spectromyographic and biochemical indices of the patients, results of their radiography and magnetic resonance tomography were analysed. Clinical-imaging-biochemical correlations were found out; they demonstrate that lumbar spinal stenosis is a clinical-structural-functional concept, whose each component being important for the formation of the above pathology.